Akibat Hukum Surat Pertanggungjawaban Laporan Tahunan Yang Tidak Ditandatangani Oleh Seluruh Dewan Komisaris - Atika Wulan Dari; Busyra Azheri; Yussy Adelina Mannas (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
The purpose of this study is to analyze how the legal consequences of the annual report accountability letter were not signed by the entire Board of Commissioners of a limited liability company by looking at the case of PT. Garuda Indonesia Tbk which occurred in 2019. Where in that case there was a rejection by 2 (two) Commissioners from PT. Garuda Indonesia Tbk to sign the annual report at the General Meeting of Shareholders. The nature of this research uses normative research, namely by reviewing laws and regulations, as well as company case reports. Based on this case, the function of company organs in charge of supervising a company is not going well. The case shows that this organ does not carry out its supervisory function in accordance with Article 108 of the Limited Liability Company Law. The legal consequence in this case is the imposition of fines on the organ of the company that signs the annual report. This is a consequence of the collegiality of the responsibility of the Board of Commissioners in a limited liability company.